Códigos de Goppa e Distâncias Generalizadas de Hamming - Lemes, Leandro Cruvinel (2009)
In this work, we study geometric Goppa codes and present several results on the so-called generalized Hamming distances. In the particular case of Hermitian codes we present precise results for the first, second and third generalized distances, for almost all Goppa codes supported on one point.